Root‐lesion nematodes of potato: Current status of diagnostics, pathogenicity and management. (4th February 2020) - Orlando, Valeria; Grove, Ivan G.; Edwards, Simon G.; Prior, Thomas; Roberts, David; Neilson, Roy; Back, Matthew
Abstract: Root‐lesion nematodes of the genus Pratylenchus are migratory endoparasites with worldwide economic impact on several important crops including potato, where certain species like P. penetrans, P. neglectus, and P. scribneri reduce the yield and quality of potato tubers. Morphological identification of Pratylenchus spp. is challenging, and recent advancements in molecular techniques provide robust and rapid diagnostics to differentiate species without the need of specialist skills. However, the fact that molecular diagnostics are not available for all Pratylenchus species means that there are limitations in worldwide application. In general, root‐lesion nematodes are difficult to manage once introduced into agricultural land and damage can be related to pathogenicity and population densities. In addition, root‐lesion nematodes interact with fungi such as Verticillium dahliae, resulting in disease complexes that enhance the damage inflicted on the potato crop. Management interventions are often focused on limiting nematode reproduction before planting crops and include the application of nematicides, and cultural practices such as crop rotation, cover crops, biofumigation, and biological control. Understanding the limitations of the available crop protection strategies is important and there are many gaps for further study. This review discusses the status of the diagnosis, distribution, pathogenicity, and management of the main species of root‐lesion nematodes, reported to infect potatoes worldwide, and highlights areas for potential future research. Abstract : Detailed review on the diagnosis, distribution, pathogenicity and management of the main species of Pratylenchus reported to infect potatoes worldwide.